Monitoring Stages of Damage in Concrete Structures by Using the Acoustic Emission Technique - Hisham A. Elfergani (African Journal of Advanced Pure and Applied Sciences, 2024)
The significant degradation caused by the corrosion of steel wire in prestressed concrete is a matter of great concern. It requires special attention in certain applications, as failure could result in not only a financial burden but also a potential loss of life. It is crucial to recognize that corrosion is not just a long-term issue; numerous studies have documented instances of bridges and concrete pipes failing shortly after construction due to corrosion. Structures such as prestressed concrete cylinder pipes (PCCP), responsible for transporting water, exemplify the impact of corrosion. The Man-Made River Project in Libya has experienced five instances of pipe failures attributable to corrosion since its installation. The primary cause of this damage is the corrosion of prestressed wires within the pipes, initiated by the infiltration of chloride ions from the surrounding soil. In the context of the Man-Made River in Libya, the early detection of corrosion is vital to prevent disruptions to water supply for homes and industries. This paper presents the application of the Acoustic Emission (AE) technique to identify and locate the initial stages of corrosion and categorize different types of cracks. The results from laboratory studies suggest that AE is effective in detecting corrosion in representative structures. Furthermore, it can distinguish and classify the location and type of cracks by analyzing AE signal parameters.